Kazakhstani Secondary Teachers’ Attitudes towards Blended Learning - Zenchuk, Irina (Nazarbayev University Graduate School of Education, 2019)
Blended learning is one of the most promising methods in modern teaching. It combines two learning environments: traditional face-to-face and online. This research is aimed at investigating Kazakhstani secondary school teachers’ attitudes towards blended learning. This qualitative research was conducted in compliance with the connectivism and social constructivism theories and was aimed at investigating Kazakhstani teachers’ attitudes towards blended learning, as well as the advantages and barriers to implementation. Preliminary data was collected through an open-ended survey from 30 teachers of different subjects to see if there was a difference in teachers’ attitudes’ depending on the subject they taught or years of their teaching experience. Based on the survey responds and participants’ willingness, five purposefully chosen teachers participated in semi-structured interviews. While analyzing the data from survey and interview coding procedure revealed some common themes which were generated into research results. Findings showed that teachers consider that blended learning catalases individualization, improves students’ engagement promotes collaboration among learners in different educational environment and makes the learning process more real-world relevant. Along with the benefits teachers mentioned challenges they face while implementing this method, such as technical issues related to the poor Internet connection, lack of materials related to the subject they teach and time-consuming lesson preparation. The research findings may be used to fulfill the gap in the literature regarding the blended learning experience in the Kazakhstani context. The research findings show that teachers are not against implementing this method. However, they should be provided with opportunities for professional development from more experienced colleagues in blended learning.
Keywords: Secondary Teachers’ Attitudes; Blended Learning; Kazakhstan; traditional face-to-face learning; online learning; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education